Menyoal Seni Lukis Indonesia Kini - -, Dharsono (Institut Seni Indoensia Surakarta, 2009)
Our painting trip since pioneering Â Â R. Saleh until the beginning of this XXI, was still swayed by the impact of conception. Indonesian art esta-blishment that has not reached the level of success, it has been devastating by western modernism that produce alternative art, with the emergence of the concept art (art conseptual):